2015
DOI: 10.1002/anie.201501715
|View full text |Cite
|
Sign up to set email alerts
|

Potential‐Dependent Adlayer Structure and Dynamics at the Ionic Liquid/Au(111) Interface: A Molecular‐Scale In Situ Video‐STM Study

Abstract: Room-temperature ionic liquids are of great current interest for electrochemical applications in material and energy science. Essential for understanding the electrochemical reactivity of these systems are detailed data on the structure and dynamics of the interfaces between these compounds and metal electrodes, which distinctly differ from those in traditional electrolytes. In situ studies are presented of Au(111) electrodes in 1-butyl-1-methylpyrrolidinium bis(trifluoromethylsulfonyl)imide ([BMP][TFSA]) by h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
133
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(145 citation statements)
references
References 54 publications
(34 reference statements)
10
133
2
Order By: Relevance
“…It was recently shown from video-STM that formation of rectangular adlayers appear at −1.0 V, which corresponded to the planar adsorption of [Py 1,4 ] + . 45 This indicates that at −1.0 V there might be again a change in the configuration of TFSI − ions which affects the angle of interaction between the methyl group in [Py 1,4 ] + and TFSI − , thereby reducing the innermost separation distance in Figure 5c. The second to fifth layers are separated by a distance of about 0.8 nm and are consistent with the presence of unaffected ion pairs.…”
Section: ■ Results and Discussionmentioning
confidence: 98%
“…It was recently shown from video-STM that formation of rectangular adlayers appear at −1.0 V, which corresponded to the planar adsorption of [Py 1,4 ] + . 45 This indicates that at −1.0 V there might be again a change in the configuration of TFSI − ions which affects the angle of interaction between the methyl group in [Py 1,4 ] + and TFSI − , thereby reducing the innermost separation distance in Figure 5c. The second to fifth layers are separated by a distance of about 0.8 nm and are consistent with the presence of unaffected ion pairs.…”
Section: ■ Results and Discussionmentioning
confidence: 98%
“…Using a broad spectrum of techniques including, e.g. photoelectron spectroscopy, vibrational spectroscopy and scanning probe microscopy, it could be shown that ILs show very specific ion-surface interactions [23][24][25], may undergo interfacial reaction [25,26], and may form layered [27][28][29] and even ordered structures at noble metal surfaces [30][31][32][33][34][35][36]. On electrochemically controlled surfaces either the cation, or the anion or both are adsorbed at the electrode surface depending on the electrode potential [30,[32][33][34][35]37].…”
Section: Introductionmentioning
confidence: 99%
“…On electrochemically controlled surfaces either the cation, or the anion or both are adsorbed at the electrode surface depending on the electrode potential [30,[32][33][34][35]37]. In their electrochemical STM studies on Au(111), for instance, Magnussen and coworkers recently showed that a variety of different ordered structures are formed as a function of the potential [30]. Atkin et al recently reviewed the pioneering work of several groups on the structure formation at IL-Au(111) interfaces [37].…”
Section: Introductionmentioning
confidence: 99%
“…We explicitly do address only studies where the targeted process is a chemical reaction between different species but do not address physical processes such as a phase transition, 59-61 adsorption or desorption, [62][63][64] and diffusion 65,66 or a reorganization. [67][68][69][70][71][72] We also exclude studies where the reaction was not carried out in situ, that is, spectra were not recorded while the reaction proceeded, or the sample was moved to a different site in the XPS setup or was even removed from the XPS setup in order to carry out the reaction. [73][74][75][76][77] We also do not address studies that incorporate electrochemical sample manipulation, 66,67,[69][70][71][78][79][80][81][82][83][84][85][86] electrodeposition of metal or organic layers from ILs, [87][88][89][90][91] and IL decomposition 84,[92][93][94][95][96][97][98][99]...…”
Section: Introductionmentioning
confidence: 99%